Raj'i Talaq Law According to the Shafi'i School in Polyandry Cases (Case Study of Banda Aceh Shar'iyah Court Decision Number 383/Pdt.G/2020/MS. Bna) - Fahmi, Mutiara; Iqbal, Muhammad; Akbar, Rizki; Nurdin, Abidin (El-Usrah: Jurnal Hukum Keluarga, 2023)
Islamic law and Indonesian legislation basically emphasize that marriage can only have one partner. In the Shafi'i school, Ash-Sharbini al-Khatib says, "A man, circumcision does not marry more than one wife without clear hajat. An-nash has pointed out that the principle of marriage is monogamy, not polygamy. The wife or a woman cannot marry more than one husband at the same time (polyandry) because of the impact caused. Polyandry is clearly forbidden as has been said by Allah Almighty. in QS. An-Nisa verse 24. In decision No. 383/Pdt.G/2020/MS. The bna polyandry is one of the reasons for divorce with the dropping of talaq one raj'i. The question in this thesis is how the right of talaq possessed by a husband how to analyze the Decision of the Judge of the Shar'iyah Court of Banda Aceh, and why the case of polyandry as a background for the breakup of marriage is broken with talaq raj'i. In this study, the author uses library research methods to analyze the judge's consideration and the Shafi'i school in terms of holding talaq rights on the grounds that they are caused by polyandry. There are several factors that make the existing legal provisions and procedures different, in the Shafi'i school in terms of privacy such as talaq is very guarded because it is considered bad if there are parties outside who know the domestic affairs, in contrast to the judge's consideration, the procedures of the Shar'iyah Court, the benefit of divorce is regulated to reduce illegal divorces that are not in accordance with the existing Shari'a. Therefore, it can be concluded that the difference that we can see between the judge's consideration and the Shafi'i school is the freedom of the husband to impose talaq anywhere and anytime, and the determination of the amount of talaq based on the husband's own intentions.